MODERN INTERPRETATIONS OF THE CONCEPT OF INVARIANT IN LINGUISTICS - Arifjanov Zokir Toxirovich (The Conference Hub, 2025)
The concept of "invariant", being the subject of study of various scientific fields, has today also acquired a philosophical meaning, which contributed to its entry into various fields of linguistics itself. Defining the meaning and importance of expanding the areas of study of the invariant in linguistics, T.V. Zherebilo provides an addition to E.T. Bell's definition of the invariant: "Despite the fact that this interpretation is self-sufficient, the definition contains two directly opposite interpretations: firstly, invariance is associated with the "general meaning"; secondly, the invariant gravitates towards the original variant, otherwise towards the primary function, which remains unchanged "despite the onslaught of countless transformations", in contrast to modifications, which are variants associated with secondary functions